Experimental Data Set of Mining-Induced Seismicity for Studies of Full-Scale Topographic Effects. Issue 1 (February 2015) - Wood, Clinton M.; Cox, Brady R.
This paper describes two large, high-quality experimental data sets of ground motions collected with locally dense arrays of seismometers deployed on steep mountainous terrain with varying slope angles and topographic features. These data sets were collected in an area of central-eastern Utah that experiences frequent and predictable mining-induced seismicity as a means to study the effects of topography on small-strain seismic ground motions. The data sets are freely available through the George E. Brown, Jr. Network for Earthquake Engineering Simulation data repository (NEEShub.org) under the DOI numbers 10.4231/D34M9199S and 10.4231/D3Z31NN4J. This paper documents the data collection efforts and metadata necessary for utilizing the data sets, as well as the availability of supporting data (e.g., high-resolution digital elevation models). The paper offers a brief summary of analyses conducted on the data sets thus far, in addition to ideas about how these data sets may be used in future studies related to topographic effects and mining seismicity.